Advanced case management strategies - Gribble, Nigel; North, T. (Safety and Rehabilitation Books, 2016)
For injured workers to be successful in their return to work programs, case managers need to be proactive in identifying the worker’s motivational factors that will enable the worker to achieve their return to work goal. All workers, no matter how long they have been off work, will be intrinsically motivated to achieve certain goals. What stands the advanced, highly successful case manager apart is their ability to uncover these specific motivations for each worker. A Long Duration Claim (LDC) is regarded as 60 or more days of lost time (WorkcoverWA, 2014) with many of these cases involving injured workers who are labelled as “complex”. Many of these workers are perceived to be unmotivated with a poor attitude or resistant to increasing hours or participating in suitable duties. This chapter will argue that all injured workers are motivated, sometimes to not participate, because of a range of reasons e.g. fear of re-injury. This chapter will propose numerous pro-active strategies that can be utilised by case managers to ensure the return to work case continues to progress. The centrepiece of this chapter is the Transtheoretical Model of Change, depicting the five stages of change that are required to achieve a successful behavioural change. Strategies discussed include motivational interviewing, case conferencing, intentional listening and a range of other advanced communication skills.